Efektivitas Kahoot terhadap Hasil Belajar Teknologi Dasar Otomotif Kelas X TKR di SMK Tamansiswa Jetis - Purnomo, Sigit; Pradona, Rendika Azis; Suparmin, Suparmin; Pratama, Kukuh Wahyudin (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to prove that the learning outcomes of Basic Automotive Technology for 10th grade students in the Automotive Engineering Department at SMK Tamansiswa Jetis in the academic year 2023/2024 are better after implementing Kahoot-based game learning. The type of research used is quantitative research, specifically a Pre-Experimental Design with a One-Group Pretest-Posttest Design. This research was conducted at SMK Tamansiswa Jetis with the population of 10th grade students in the Automotive Engineering Department. The sampling technique used in this research was Total Sampling. The research sample consisted of one class of 33 students from the 10th grade in the Automotive Engineering Department. Data collection techniques included interviews, test questions (pre-test and post-test), and documentation. The research instruments used multiple-choice pre-test and post-test questions. Data analysis techniques included descriptive statistics and inferential statistics with prerequisite analysis tests including normality test and hypothesis testing using paired sample t-test to determine the effect of variable X on variable Y. The results of the study showed that the learning outcomes of Basic Automotive Technology for 10th grade students in the Automotive Engineering Department at SMK Tamansiswa Jetis in the academic year 2023/2024 were better after implementing Kahoot-based game learning